Comparative analysis of videolaparoscopic appendectomy in the SUS: Ceará and the Northeast Region (2020–2024) (Research, Society and Development, 2025)
This study analyzes the epidemiological and financial data of videolaparoscopic appendectomies performed by the Brazilian Unified Health System (SUS) between 2019 and 2024 in the state of Ceará and in the Northeast region. This is a quantitative and descriptive study based on public DATASUS data, evaluating the number of hospital admissions, hospital expenses, professional fees, average length of stay, deaths, and mortality rate. During the analyzed period, Ceará registered 1,909 admissions, corresponding to 28.5% of the total in the Northeast, with an average cost per admission of R$ 638.79, which is 5.6% lower than the regional mean. However, a longer average hospital stay (4.2 days versus 3.3 days in the Northeast) and a higher proportional mortality rate (0.26% versus 0.12%) were observed. These findings suggest possible structural and organizational differences between the state and the region, reflecting inequalities previously described in the literature regarding installed capacity, service organization, and patient profiles. The discrepancies may also be influenced by limitations inherent to the use of secondary data, such as underreporting and the absence of detailed clinical information, which require caution when interpreting the results. In conclusion, despite the favorable financial performance, Ceará showed higher length of stay and mortality, indicating the need to improve care pathways, enhance data quality, and strengthen strategies to increase efficiency and equity within SUS.